Earnings management around founder CEO reappointments and successions in family firms. (6th May 2021) - Ansari, Iram F.; Goergen, Marc; Mira, Svetlana
Abstract: This paper studies reappointment of a chief executive officer (CEO) and succession events in listed family firms with an incumbent family CEO. We explore whether family firms with a founder CEO are more likely to engage in earnings management preevent than other family firms. We find evidence of preevent upward earnings management for firms that reappoint their founder CEO but no for other family firms. These findings suggest that the costs and benefits from earnings management change around founder CEO reappointments in family firms. Investors, auditors, policymakers and regulators should be aware of the temptation of founder CEOs to inflate earnings preceding their reappointment.